Vulnerable groups in Malaysia - Kananatu, Thaatchaayini; Koh, Sharon G. M. (Berlin : De Gruyter, 2020)
Vulnerability is a term that can be studied from different dimensions ? the social, legal, economic and political. This book explores these dimensions and captures the vulnerabilities of particular groups in Malaysia ? the transgenders, women, children, aboriginal and indigenous people, the rural fisherfolk, the stateless and the economically disempowered. Mirroring the spectrum of 'vulnerable groups' defined by the United Nations Global Compact in the 2016 Sustainable Development Goals Report, this book highlights the unique features that portray vulnerabilities ? including gender, age, indigeneity, socioeconomic status and ethnicity. The case studies of vulnerable groups in Malaysia ? a multicultural, diverse plural Asian state ? would be appreciated by both undergraduate and postgraduate students, academics, researchers and policy-makers, keen in Asian Studies and vulnerabilities.
Intro -- Acknowledgements -- Contents -- 1. Vulnerability and the vulnerable in an Asian plural state -- Section One: Gender -- 2. The trans community as outliers of Malaysian society -- 3. Negotiating womanhood: Vulnerability in the pursuit of beauty -- Section Two: Children -- 4. Caught in a rights gap: The Malaysian child in conflict with the law -- 5. Assessing underprivileged students' academic performance and absenteeism level in a values-based education -- Section Three: Indigenous people -- 6. The vulnerability of the aboriginal community in relation to customary land rights -- 7. The fallacy of economic upliftment through ecotourism: The case of the Malaysian indigenous Orang Asli -- Section Four: The economically and politically disadvantaged -- 8. Can we avoid the tragedy of the commons? Managing the vulnerability of the fishing community in Malaysia -- 9. Statelessness as the conduit to rights for the stateless Indian community in Malaysia -- 10. The financial vulnerability of Indian micro and small entrepreneurs in Malaysia -- 11. The vulnerable in Malaysia: Moving forward -- Notes on contributors -- List of Figures -- List of Tables -- Index.
Keywords: Minorities -- Malaysia -- Case studies; Women -- Malaysia -- Case studies; Children -- Malaysia -- Case studies